A Faulty PK Meta-Analysis - Wilfried Kugel (Journal of Scientific Exploration, 2011)
Abstract—This article starts with an introduction to the concepts and experimental methodology used in the investigation of micro-psychokinesis (micro-PK). After a summary of three PK meta-analyses that seem to show a genuine PK effect, I will comment on a paper by Holger Bösch, Fiona Steinkamp, and Emil Boller (BSB), entitled “Examining Psychokinesis: The Interaction of Human Intention With Random Number Generators—A Meta‑Analysis” (BSB-MA). The paper was published in the July 2006 issue of the Psychological Bulletin and suggests that all evidence of micro-PK may be due to publication bias. I will then show that the BSB-MA contains a large number of serious errors, which include data selection bias, faulty data coding, a lack of correspondence between experimental and control datasets, faulty statistical analyses, and erroneous interpretation of results. In addition, the entire negative z-score in the meta‑analysis results from only one study. This meta-analysis, therefore,  produced spurious results.